2021
DOI: 10.3390/jcm10040687
|View full text |Cite
|
Sign up to set email alerts
|

Is There Pathological Uniformity between the Periphery and Center of a Gastrointestinal Stromal Tumor?

Abstract: Background: Gastrointestinal stromal tumors (GISTs) are mesenchymal tumors and have some malignant potential. Mitotic count is important for predicting the malignant potential of GISTs. Proper treatment of GISTs requires accurate pathological diagnosis. In general, endoscopic ultrasound-guided fine-needle aspiration and deep biopsy are used for pathological diagnosis of GIST before making decisions about surgery. This study sought to evaluate the pathological uniformity of gastric GISTs for mitotic index of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…In our study, no significant association was found between risk and age groups or gender. This is in line with some literature suggesting that while age and gender may influence the incidence and prevalence of GISTs, their impact on the risk or prognosis of these tumors is less clear [23,24] . However, contradictory findings exist, with a few studies suggesting a worse prognosis for older patients or a particular gender [25,26] .…”
Section: Discussionsupporting
confidence: 91%
“…In our study, no significant association was found between risk and age groups or gender. This is in line with some literature suggesting that while age and gender may influence the incidence and prevalence of GISTs, their impact on the risk or prognosis of these tumors is less clear [23,24] . However, contradictory findings exist, with a few studies suggesting a worse prognosis for older patients or a particular gender [25,26] .…”
Section: Discussionsupporting
confidence: 91%